2022
DOI: 10.1016/j.jpsychires.2022.01.032
|View full text |Cite
|
Sign up to set email alerts
|

An international cross-sectional investigation on social media, fitspiration content exposure, and related risks during the COVID-19 self-isolation period

Abstract: With the global COVID-19 pandemic, governments from many countries in the world implemented various restrictions to prevent the SARS-Cov-2 virus's spread, including social distancing measures, quarantine, in-home lockdown, and the closure of services and public spaces. This led to an in-creased use of social media platforms to make people feel more connected, but also to maintain physical activity while self-isolating. Concerns about physical appearance and the desire to keep or reach a muscular and toned idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
5
11
0
5
Order By: Relevance
“…It is already known that social media plays a large part in shaping and predicting ED behaviours [33,34] due to their tendency to promote social comparison [35], particularly content that focused on "fitspiration" [36]. Within the context of COVID-19, it was found that exposure to fitness-related content on social media led to greater appearance anxiety during this period [37], thereby corroborating the present study findings.…”
Section: Influences Of Social Mediasupporting
confidence: 89%
“…It is already known that social media plays a large part in shaping and predicting ED behaviours [33,34] due to their tendency to promote social comparison [35], particularly content that focused on "fitspiration" [36]. Within the context of COVID-19, it was found that exposure to fitness-related content on social media led to greater appearance anxiety during this period [37], thereby corroborating the present study findings.…”
Section: Influences Of Social Mediasupporting
confidence: 89%
“…On social media they are literally looking for nutrition, health and fitness information whilst the focus often is on physical improvement. In line, the findings of a recent study by Cataldo et al [3] have revealed that, in particular during the Covid-19 pandemic, the social and fitness-related use of social media is significantly increased. Aside, the discussion about the socially embossed body ideal is omnipresent.…”
Section: Introductionsupporting
confidence: 84%
“…Seventeen studies showed that exposure to "fitspiration" images led to increased body dissatisfaction [ 15 , 18 , 36 46 , 48 50 , 56 ]. The study carried out by Krug et al demonstrated a neutral effect of fitspiration content on body image [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings demonstrate fitspiration was related to poorer body image perceptions among students. Weak Cataldo et al [ 56 ] Cross-sectional study 729 Participants (527 females; 202 males); mean age: 37,8 ± 11,68 years; Examine the role of social media influence as a possible factor contributing to a set of connected issues attributable to the fitspiration construct. 1.…”
Section: Methodsmentioning
confidence: 99%